2016
DOI: 10.1186/s12936-016-1451-y
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific escape of Plasmodium sporozoites from oocysts of avian, rodent, and human malarial parasites

Abstract: BackgroundMalaria is transmitted when an infected mosquito delivers Plasmodium sporozoites into a vertebrate host. There are many species of Plasmodium and, in general, the infection is host-specific. For example, Plasmodium gallinaceum is an avian parasite, while Plasmodium berghei infects mice. These two parasites have been extensively used as experimental models of malaria transmission. Plasmodium falciparum and Plasmodium vivax are the most important agents of human malaria, a life-threatening disease of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
(48 reference statements)
1
17
0
Order By: Relevance
“…This raises the question as to whether the processes of oocyst egress are conserved in human malaria parasites. Orfano et al (2016) showed that the mechanism for sporozoite egress from the oocyst differs among Plasmodium species. P. berghei and the avian malaria parasite Plasmodium gallinaceum appear to egress similarly, breaking the oocyst wall.…”
Section: Oocyst Egressmentioning
confidence: 99%
“…This raises the question as to whether the processes of oocyst egress are conserved in human malaria parasites. Orfano et al (2016) showed that the mechanism for sporozoite egress from the oocyst differs among Plasmodium species. P. berghei and the avian malaria parasite Plasmodium gallinaceum appear to egress similarly, breaking the oocyst wall.…”
Section: Oocyst Egressmentioning
confidence: 99%
“…Analysis of rodent or avian model systems can yield interesting results, but human, avian and rodent Plasmodium have been shown to develop differently within the vector [49], raising questions about how reliably this data can be extrapolated to human systems.…”
Section: Box 1 Potential Confounding Factors Between Laboratory and Fmentioning
confidence: 99%
“…However, it also raises additional questions about the confidence with which inferences drawn from the results can be extended to real-world human populations. For example, it has been shown that Plasmodium oocysts develop differently in human, rodent and avian hosts [49], which may also impact immune responses. Only two host-seeking studies have been carried out with the human malaria parasite, P. falciparum, with one reporting increased short-range hostseeking by An.…”
Section: Challenges In Extrapolating Findings Across Diverse Systemsmentioning
confidence: 99%
“…Regrettably, these strategic measures are pretty less operative due to the swift evolvement and proliferation of resistance against extensively utilized insecticides and drugs [10,11]. Taking advantage of the genomic sequences of the malaria vectors and parasites may eventually result in new generations of insecticides and drugs, the upcoming of an efficient vaccine or genetically altered mosquitoes [12][13][14]. Unfortunately, these novel intervention measures may be inaccessible for the next ten years.…”
Section: Introductionmentioning
confidence: 99%